The evolution of genetic counseling graduate education in New York City during the COVID‐19 pandemic: In the eye of the storm. Issue 4 (3rd July 2021) - Bergner, Amanda L.; Ecker, Lindsey Alico; Ernst, Michelle E.; Goelz, Monika Zak; Habermann, Kristina; Karger, Lisa; Zinberg, Randi E.
Abstract: The COVID‐19 pandemic has ravaged the globe in the past year, demanding shifts in all aspects of life including health profession education. The New York City area was the first major United States epicenter and is home to four genetic counseling graduate programs. We set out to explore the multifaceted programmatic changes required from the four institutions in an early pandemic epicenter, providing the longest time horizon available for assessing the implications of this restructuring on graduate education in the profession. Using practitioner‐based enquiry, our iterative reflections identified three phases of COVID‐19 response within our programs from March through December 2020. The spring months were marked by significant upheaval and reactivity, with a focus on stabilizing our programs in an unstable environment that included a significant medical response required in our area. By summer, we were reinvesting time and energy into our programs and prioritizing best practices in online learning. Relative predictability returned in the fall with noticeable improvements in flexibility and proactive problem‐solving within our new environment. We have begun to identify changes in both curricula and operations that are likely to become more permanent. Telehealth fieldwork, remote supervision, simulated cases with standardized clients, and virtual recruitment and admission events are some key examples. We explored early outcome measures, such as enrollment, retention, course evaluations, and student academic and fieldwork progress, all indicating little change from prior to the pandemic to date. Overall, we found our programs, and genetic counseling graduate education more broadly, to be much more resilient and flexible than we would ever have realized. The COVID‐19 pandemic has awakened in us a desire to move ahead with reduced barriers to educational innovation.